2006
DOI: 10.1080/13596740600769230
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the webquest as a computer‐based learning tool

Abstract: This paper explores the preparation and use of an internet activity for undergraduate learners in higher education (HE). It evaluates the effectiveness of using webquest as a computer-based learning (CBL) tool to support students to learn in HE. The evaluation undertaken offers insights into learner perceptions concerning the ease of use of the webquest, the success of the learning experience and the adequacy of the interaction and engagement afforded. Although displaying some significant strengths, the webque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
2
23
0
4
Order By: Relevance
“…According to teacher candidates, the Webquests can teach students how to search the Internet. The students who participated in a study by Hassanien [16] for the of the effectiveness of the Webquests on the learning of the higher education students and the productivity of the Webquest as a CBL (Computer Based Learning) tool also expressed similar views. They found that Webquest positively contributes to learning experiences and that they are satisfied with their learning experiences, and that they can learn from the Internet.…”
Section: Discussion and Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…According to teacher candidates, the Webquests can teach students how to search the Internet. The students who participated in a study by Hassanien [16] for the of the effectiveness of the Webquests on the learning of the higher education students and the productivity of the Webquest as a CBL (Computer Based Learning) tool also expressed similar views. They found that Webquest positively contributes to learning experiences and that they are satisfied with their learning experiences, and that they can learn from the Internet.…”
Section: Discussion and Resultsmentioning
confidence: 90%
“…According to Patterson and Pipkin [15], Webquest is an effective way to help students acquire new knowledge as a guide in the learning environment and to organize irregular Internet resources. Given these definitions, it can be said that Webquest is a teaching method that helps students to research and solve the problems, using the Internet as a tool [16].…”
Section: What Is Webquest?mentioning
confidence: 99%
“…A relevant and plausible question is whether the use of our peerless e-modules increased learning outcomes and performance. This issue was not addressed even though Zozie, (2017); Douglas, et.al., (2012) ;Hassanien, (2006);Laru, et.al., (2012) andSingh, (2010) predicted that e-learning tools may improve learning experiences. In fact, identifying how learning tools affect learning outcomes seems difficult because of the so many variables that come into play when measuring such behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Lipscomb [16] identified that WebQuest method contributes to the development of creativity. Hassanien [17] indicated that WebQuest method makes it possible to gather information form the Internet as well as it is helpful to get access to information sources. All these findings are in line and complementary with this research.…”
Section: Discussionmentioning
confidence: 99%